IMPRESSION OF UNORGANIZED RETAILERS TOWARDS B2B WHOLESALERS - METRO AND BEST PRICE (International Journal of Food and Nutritional Sciences, 2019)
Retailing stands as a pivotal industry in India, serving as a major employment source andwitnessing rapid growth. Global giants such as Wal-Mart and Metro, alongside domesticplayers like Reliance and Aditya Birla Group, contribute to the evolving retail landscape.Organized retailing gains prominence, offering future enhancements.